Evaluation of Pangkabuhayan Qcitizens Program to the Vendors of Commonwealth Market, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study evaluates the Pangkabuhayn Qcitizens program to the vendors of Commonwealthmarket, Quezon City, in terms of financial stability, business stability, and their problemencounters to avail of the financial assistance business program.The results of this study show that the evaluation of financial assistance programs is“Relatively stable” in terms of financial stability, business stability, and other business sources.They have their own capability how to improve their business using the financial assistancebusiness program; the problem encountered to availed financial assistance business programis they don’t have the ability to get the Quezon city identification (I.D)The study recommended that the financial assistance business program of Mayor JoyBelmonte in Quezon City is will they continue to provide and give financial assistancebusiness program to every vendor on the sidewalk who needs it because they lose their profitand their income to support their family needs.
Keywords: Business